Ayurvedic Perspective and Approach in Age-Related Macular Degeneration - Anil Kumar; Rajendra Kumar Soni (AYUSHDHARA, 2024)
Age-Related Macular Degeneration (ARMD) is a bilateral, chronic, degenerative illness that primarily affects the macula while leaving the peripheral retina mostly unaffected. As it is the maculopathy affecting the central vision, people experience difficulty in day-to-day routine work and reduction in quality of life and bear depression. In Ayurveda, Drishtigata Rogas results in partial to complete loss of vision. Pitta Vidagdha Drishti is one of the diseases of Drishtigata Roga. As the underlying pathophysiology of the condition, Pitta (which is principally responsible for vision) vitiates and aggravates. When this vitiated and provoked Pitta affects the Drishti (macular portion of the retina), it eventually results in Vidagdhata (inflammation, ulceration, and degeneration of the local tissue), it results in a clinical picture resembling the now-known age-related macular degeneration (ARMD). As it is described as an Ashatrakrita Pittaja Vyadhi and the treatment of this disease is given briefly in Samhitas it is important to conduct study on such topic and come to a proven beneficial Ayurvedic management. The Ayurvedic review of age related macular degeneration and its potential correlation with Pitta Vidagdha Drishti is the primary focus of this paper.